Nitrogen and Sulfur Oxides Emissions from Fuel Oil Combustion in Industrial Steel Reheat Furnace (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Many industrial heating operations still use fueloil for combustion instead of the cleaner gaseous fuels. Inthe steel industry, large furnaces referred to as reheat furnaces are used to heat steel stocks to rolling temperaturesusing normally fuel oil for combustion. The combustionproducts of flue gases consist of mainly carbon dioxide,water vapor and traced of other oxides such as nitrogen andsulfur oxides. These oxides are of a concern to theenvironment and should be minimized as much as possible.Experiments were carried out on a steel billet reheatfurnace in which air/fuel ratios are varied while the nitrogenoxide content is being monitored using furnace instruments.These variations in air/fuel ratios for combustion are foundto affect the concentration of nitrogen oxides in the flue gaswhere higher air/fuel ratios promoted the formation ofhigher nitrogen oxides during combustion. The sulfurdioxide content in the flue gas was calculated based onactual measurements of air and fuel rates to the furnace andfound to be minimal in the flue gas.